Evidence for a primitive deep mantle component in the source of Marquesas Islands Lavas from Os isotope and highly siderophile element abundance systematics. (15th July 2022) - Nicklas, Robert W.; Day, James M.D.; Jones, Timothy D.; Castillo, Paterno R.
Abstract: The Marquesas islands are an age-progressive volcanic chain in French Polynesia formed by partial melting above a mantle plume. Previous studies have demonstrated the presence of an enriched mantle (EM2) endmember mixed with a high- 3 He/ 4 He (up to 14.4 RA ) component in Marquesas post-shield lavas. In contrast, Marquesas shield lavas sample a dilute high-μ (HIMU) type component with lower 3 He/ 4 He (∼8 RA ). We report new incompatible trace element and highly siderophile element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances and osmium isotope data for bulk rocks from the islands of Fatu Hiva, Hiva Oa and Nuku Hiva, for which He, Sr, Nd and Pb isotope compositions have been reported previously (Castillo et al., 2007 ). As the HSE are chiefly hosted in sulfide phases in the mantle and all but Re are compatible during partial melting, they offer information on both sulfide-rich and melt-depleted mantle lithologies within the Marquesas plume. Primitive mantle-normalized HSE abundances show depletions in Ru and Pd, and fractionated (Ir/Os)N in fourteen of the seventeen analyzed samples. Ruthenium depletions and Ir-Os fractionations are likely caused by parental magma fractional crystallization. Palladium depletions are not easily explained by magmatic or secondary alteration processes and are instead likely to be a feature of the source mantle which was partially depleted in the more incompatible HSE by previous melting events within the Marquesas plume. Osmium isotopic systematics are mildly radiogenic relative to chondrites and are identical within uncertainties for shield-building Fatu Hiva (γOs = +2.9 ± 1.6; 2 SD; n = 7) and post-shield Hiva Oa (+2.7 ± 2.2; n = 9), showing no evidence for significant assimilation of radiogenic oceanic crust. The osmium budget of Marquesas lavas is controlled by a volumetrically dominant peridotite endmember that is incompatible element depleted while the Sr, Nd, and Pb budgets are strongly influenced by a volumetrically minor, incompatible element enriched EM2 component. The Nd-Sr-Os isotope systematics of the lavas can be explained by mixing of 0.3–0.7% of an EM2 type melt into the Marquesas source. Marquesas lavas offer further support that the high- 3 He/ 4 He "focus zone" (FOZO) mantle has 187 Os/ 188 Os mildly more radiogenic than the depleted upper mantle, similar to estimates of the primitive mantle. Osmium isotope systematics offer a useful tool with which to characterize more depleted components within the ocean island basalt-source mantle that may be difficult to detect using lithophile isotope signatures.